Modeling of surface electromagnetic waves with axial symmetry on a bi-isotropic one-layer plane screen - V. T. Erofeenko (Informatika)
A homogeneous three-domain boundary-value problem for a one-layer plane screen from a bi-isotropic material is formulated. Monochromatic electromagnetic fields with axial symmetry propagating behind the screen, in front of the screen and into the screen layer are calculated. Classical boundary conditions of the continuity of the tangential field components on the planes of media separation are used. To simplify the procedure of constructing analytical solutions, the original problem is transformed into a boundary problem with two-sided boundary conditions connecting electromagnetic fields on both sides of the screen. As a result, the field in the screen layer is excluded from consideration. A method for calculating surface electromagnetic waves with axial symmetry, propagating from two sides of the screen in the radial directions of the layers, is developed. A screen from a chiral material is considered as a bi-isotropic screen. For chiral screen a second-order dispersion equation was obtained, which made it possible to calculate the frequencies of the two sequences of surface electromagnetic fields. The parameters of the chiral material for which non-attenuating surface waves exist are calculated. Surface waves are presented as a combination of basis cylindrical TE- and ТЯ-polarized electromagnetic fields. Other variants of surface waves are possible.